Datasets on the statistical and algebraic properties of primitive Pythagorean triples - Hilary I. Okagbue; Muminu O. Adamu; Pelumi E. Oguntunde; Abiodun A. Opanuga; Enahoro A. Owoloko; Sheila A. Bishop (Data in Brief, 2017)
The data in this article was obtained from the algebraic and statistical analysis of the first 331 primitive Pythagorean triples. The ordered sample is a subset of the larger Pythagorean triples. A primitive Pythagorean triple consists of three integers a, b and c such that; a2+b2=c2. A primitive Pythagorean triple is one which the greatest common divisor (gcd), that is; gcd(a,b,c)=1 or a, b and c are coprime, and pairwise coprime. The dataset describe the various algebraic and statistical manipulations of the integers a, b and c that constitute the primitive Pythagorean triples. The correlation between the integers at each analysis was included. The data analysis of the non-normal nature of the integers was also included in this article. The data is open to criticism, adaptation and detailed extended analysis.